Democracy and schooling: The paradox of co‐operative schools in a neoliberal age?. Issue 6 (28th October 2022) - Woodin, Tom; Gristy, Cath
Abstract: From the first co‐operative trust school at Reddish Vale in Manchester in 2006, the following decade would witness a remarkable growth of 'co‐operative schools' in England, which at one point numbered over 850. This paper outlines the key development of democratic education by the co‐operative schools network. It explains the approach to democracy and explores the way values were put into practice. At the heart of co‐operativism lay a tension between engaging with technical everyday reforms and utopian transformative visions of an educational future. A new arena of debate and practice was established with considerable importance for our understanding of democratic education within the mainstream.